2017
DOI: 10.1007/s13312-018-1222-7
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Continuous Positive Airway Pressure in Bronchiolitis: A Randomized Controlled Trial

Abstract: nCPAP helped reduce respiratory distress significantly compared to standard care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 12 publications
(16 reference statements)
2
37
0
2
Order By: Relevance
“…Our final screening revealed that 9 eligible papers underwent qualitative analysis (a total of 9 studies). [30][31][32][33][34][35][36][37][38] Only 7 studies were included for quantitative analysis consisting of 6 retrospective studies and 1 randomized controlled trial. Figure 1 shows the PRISMA flow chart 25 to illustrate the study selection process.…”
Section: Literature Search and Selectionmentioning
confidence: 99%
“…Our final screening revealed that 9 eligible papers underwent qualitative analysis (a total of 9 studies). [30][31][32][33][34][35][36][37][38] Only 7 studies were included for quantitative analysis consisting of 6 retrospective studies and 1 randomized controlled trial. Figure 1 shows the PRISMA flow chart 25 to illustrate the study selection process.…”
Section: Literature Search and Selectionmentioning
confidence: 99%
“…A total of 7 trials were identified describing important physiological findings. There were several physiological studies either using a cross over or a randomised controlled trial design (8,(37)(38)(39)(40)(41). All of these physiological studies, with some being reported as early as the 1990's, demonstrated significant improvement in either respiratory mechanics, work of breathing or gas exchange with improved CO2 clearance or oxygenation.…”
Section: Physiological Studiesmentioning
confidence: 99%
“…In China, respiratory departments have demonstrated wide application and good clinical efficacy of nCPAP; however, some key problems have not been solved. There is no uniform standard for setting and titrating positive endexpiratory pressure (PEEP) level, which is paramount to the effectiveness of the treatment (4,5). This prospective study between December 2018 and February 2019, compared the clinical efficacy of nCPAP at various PEEP levels in the treatment of severe bronchiolitis; changes in the degree of airway obstruction and respiratory mechanics parameters were also assessed.…”
Section: Introductionmentioning
confidence: 99%